PENGARUH OPINI AUDIT TERHADAP KINERJA PEMERINTAH DAERAH DENGAN REALISASI PENDAPATAN DAN BELANJA DAERAH SEBAGAI VARIABEL INTERVENING - Anthonius H. Citra Wijaya; Andika Rante; Putri Inda Ramandey (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2018)
This study aims to obtain empirical evidence about the effect of audit opinion on the performance of local governments with the realization of regional revenues and expenditures as an intervening variable in empirical studies in district and city governments in the Papua Province. Regional income is reflected in the value of absolute logarithm natural total Regional Original Income. Regional expenditure is reflected in the value of absolute natural logarithms in total Operating Expenditures.Government performance is reflected in the score of the evaluation results of SAKIP implementation. This study used 28 districts and 1 city as samples from local governments in Papua Province. The sample is determined using purposive sampling. The results of this study indicate that the audit opinion does not have a direct effect on the performance of the local government or after it has been mediated by local revenue and operating expenses. Audit opinion affects Regional Original Revenue. Regional Original Income does not affect the Performance of Local Governments. Audit Opinion has an effect on Operational Expenditures and Shopping Expenditures does not affect the Performance of Local Government